Knowledge and Attitudes Against Covid-19 Prevention Behavior of Public Health Students - Mukhlasin, Mukhlasin; Hayat, Fauzul (KnE Social Sciences, 2023)
This observational quantitative research uses cross-sectional approach. The sample in this study amounted to 42 respondents who were taken using accidental sampling. Data were collected in the form of primary data using mixed questionnaires. The research was conducted in May – Juni 2022 at Faletehan University. Data were analyzed through univariate and bivariate analysis. The results of the univariate analysis showed that from 42 respondents, 15 (35,7%) public health students had poor behavior, 16 (38,1%) had poor knowledge levels, and 13 (31,0%) public health students behaved unfavorably. The results of the bivariate analysis with α = 0.05 showed that one variable related to Covid-19 prevention behavior, namely attitude with (p-value = 0.0035). On the other hand, the variable which was not related to Covid-19 prevention behavior was in knowledge level with (p-value = 08875). The conclusion is that there is a relationship between the attitude of public health students of Universitas Faletehan with Covid-19 prevention behavior. The most important and most instrumental thing in preventing Covid-19 behavior is to use a mask and wash hands using soap after handling something. Keywords: attitude, Covid-19, knowledge level, prevention behavior